Vitamin A intake forms resistance to hypervitaminosis A and affects the functional activity of the liver - Bozhkov, Anatoly; Ionov, Igor; Kurhuzova, Nataliia; Novikova, Anna; Katerynych, Оleg; Akzhyhitov, Rustam (My University, 2022)
Disruption of the exchange of copper ions in the body is accompanied by the development of a number of pathologies and, most often, liver fibrosis. Ito cells, which deposit vitamin A, play a key role in fibrogenesis. For the purpose of determining the impactof vitamin A on the functional characteristics of the liver with fibrosis, we studied the dynamics of vitamin A accumulation in the liver during its daily administration (up to 21 days) in intact animals and animals with Cu-induced liver fibrosis, as well as physiological (body weight and relative weight organs) and biochemical parameters (activity of alanine aminotransferase, alkaline phosphatase, concentration of cholesterol and urea). It was shown that daily administration of vitamin A to experimental animals at a dose of 300 IU/100 g of body weight was accompanied by its accumulation in the liver, and, after reaching a concentration of 250e300 mg/g, its content decreased even against the background of further administrations. The development of Cu-induced liver fibrosis was accompanied by a decrease in vitamin E in the liver by 40% compared with the baseline level. The administration of vitamin A to animals with liver fibrosis was also accompanied by its accumulation in the liver, but its increase was observed later, and the rate of decrease was faster. There is an inverse relationship between the vitamin A content and the vitamin E content in the liver. Administration of vitamin A to animals with liver fibrosis was accompanied by normalization of ALT activity, cholesterol content, and restoration of the growth rate of animals
Vitamin A intake forms resistance to hypervitaminosis A and affects the functional activity of the liver / Anatoliy Bozhkov, Igor Ionov, Nаtalia Kurhuzova, Anna Novikova, Оleg Katerynych, Rustam Akzhyhitov // Clinical Nutrition Open Science. – 2022. –V. 41. – P. 82–97.
Keywords: вітамін A, фіброз, гіпервітаміноз, антиоксидантна система; vitamin A, fibrosis, hypervitaminosis, antioxidant system